Probable Maximum Precipitation (PMP) Analysis for Bakun Dam Area - Yiau, S.S.; F.J., Putuhena (Universiti Malaysia Sarawak, 2011)
Probable Maximum Precipitation is defined as the greatest depth of precipitation which is possible for a given time and duration over a given size storm area under known meteorological conditions. This concept has been used as design criterion of major flood control measures such as spillways of large dams worldwide. It is essential for the generation of Probable Maximum Flood. This paper represents the results of PMP analysis for Bakun Dam Area which has a catchment area of 14,750 km2. Three sets of results were produced, i.e. by statistical method (with frequency factors from World Meteorological Organization manual and National Hydraulic Research Institute of Malaysia in Technical Research Publication No. 1 (TRP 1)) for duration of 1 hour, 8 hours, 24 hours and daily and by experimental method for production of daily PMP. The results were compared with each other and the one made by Sarawak Electricity Supply Corporation on Bakun Dam construction. The set of PMP values results from substitution of Km developed by NAHRIM was concluded to be the most reliable results as daily PMP (276mm) was consistent with the one (280mm) produced by SESCO. However, 6 days PMP value (950mm) done by SESCO was recommended as the Bakun Dam Area cover huge catchment area which higher duration of PMP value should be applied.